MALPRAKTIK DAN CONTEMPT OF COURT - Huda, Afiful; Sprinda, Mila Novia (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2024)
The research discusses two different legal phenomena that often influence public trust in the judicial system and certain professions in Indonesia. First, malpractice, which refers to unprofessional conduct by individuals in various professions such as medical, legal, accounting, and others. Second, Contempt of Court, which involves actions considered to insult or undermine the dignity of the court. In the first part, the definition and types of malpractice are outlined, with an emphasis on errors and negligence leading to patient harm or even death. This phenomenon is linked to differences in ethics, codes of conduct, and underlying legal violations. Furthermore, the discussion of Contempt of Court highlights behaviors deemed to insult or harm the credibility of the court. In the Indonesian context, the lack of specific regulations has led to the spread of this offense across various articles in criminal law, making law enforcement and consistent understanding of actions considered as "contempt" difficult. This research emphasizes the urgency of clearer and more detailed regulations regarding both phenomena to ensure justice, integrity, and public trust in the Indonesian judicial system. With more specific rules in place, it is hoped that the public will become more aware of the importance of respecting and complying with existing legal norms. Concrete cases of malpractice and Contempt of Court provide real-life examples of how these phenomena impact daily life, both through loss of life and serious disruptions to the judicial process. This underscores the need for concrete action to improve the judicial system and ensure that all parties, including the professionals involved, are accountable for their actions and decisions.